Operational excellence 2025: cultivating a culture of continuous improvement - Abd Rahman, Zanariah; Mat Din, Syaidatul Zarina; Othman, Akmal Aini; Elias, Suhaidi (Universiti Teknologi MARA, Johor, 2025)
Increasingly challenging higher education landscape, universities are expected not only to provide quality teaching and learning but also to ensure that administrative systems and support services operate at an optimal level. Operational excellence can be defined as a work philosophy that emphasizes continuous improvement, process effectiveness, and prudent resource management to deliver consistent, reliable, and customer-oriented services (Liker, 2021). Through the OE Unit, UiTM Johor Branch can coordinate process improvement efforts more systematically, ultimately contributing to the enhancement of the overall organizational quality.